2021
DOI: 10.1186/s12935-021-02257-4
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal transfer of miR-769-5p promotes osteosarcoma proliferation and metastasis by targeting DUSP16

Abstract: Background Osteosarcoma (OS) is a malignant tumor originating from mesenchymal stem cells, and has an extremely high fatality rate and ability to metastasize. Although mounting evidence suggests that miR-769-5p is strongly associated with the malignant progression and poor prognosis of various tumors, the exact role of miR-769-5p in OS is still unclear. Therefore, this study aimed to explore the relationship between miR-769-5p and the malignant progression of OS, and its underlying mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…miR-769-5p suppressed cell proliferation, migration, and invasion targeting TGFBRI mRNA in non-small cell lung carcinoma [35]. Conversely, in osteosarcoma, it has been demonstrated to promote cell proliferation, invasion and metastasis by targeting the phosphatase DUSP16 [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-769-5p suppressed cell proliferation, migration, and invasion targeting TGFBRI mRNA in non-small cell lung carcinoma [35]. Conversely, in osteosarcoma, it has been demonstrated to promote cell proliferation, invasion and metastasis by targeting the phosphatase DUSP16 [23].…”
Section: Discussionmentioning
confidence: 99%
“…Figure2) [20][21][22]. Moreover, data from the literature reported that miR-769-5p is loaded into osteosarcoma-derived EVs [23]. In this frame, we wondered whether the here demonstrated reprogramming activity of miR-769-5p could be horizontally transferred via EVs.…”
Section: Wt1-mediated Induction Of Mir769-5p Is Repressed In Fibrotic...mentioning
confidence: 94%
“…The difference analysis of miR‐769‐5p was conducted through the TCGA database. Literatures reported that miR‐769‐5p has a role in the tumour as an oncogenic miRNA in hepatocellular carcinoma, osteosarcoma, glioma and so on 16–19 . However, the role of miR‐769‐5p in cisplatin resistance in GC has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Literatures reported that miR-769-5p has a role in the tumour as an oncogenic miRNA in hepatocellular carcinoma, osteosarcoma, glioma and so on. [16][17][18][19] However, the role of miR-769-5p in cisplatin resistance in GC has not been reported. Therefore, the purpose of this study was to explore the relationship and mechanism between miR-769-5p and cisplatin resistance in GC.…”
Section: Introductionmentioning
confidence: 99%
“…There are similar phenomena in osteosarcoma. Most studies have shown that BMSCs promote the progression of osteosarcoma, and its mechanism includes the role of transferring exosome [ 38 ]. Interestingly, Zhou et al found that BMSCs can transfer miR-1913 into osteosarcoma cells through exosomes, reduce the expression level of NRSN2, and play a role in inhibiting the proliferation, migration and invasion of osteosarcoma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%